2021
DOI: 10.1017/s0007114521003020
|View full text |Cite
|
Sign up to set email alerts
|

Use of parenteral nutrition in term and late preterm infants: an Australian and New Zealand survey

Abstract: There is limited information regarding the use of parenteral nutrition (PN) in term and late preterm infants. We conducted a survey to study the current clinical practices within Australia and New Zealand (ANZ). A 15-question online-survey was distributed to 232 neonatologists and 55 paediatric intensivists across ANZ between September and November 2019. At least one neonatologist from 27 out of 30 tertiary neonatal intensive care units responded (90%). Responses were received from 69 neonatologists (30%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…For the prescription of parenteral nutrition, 61% (46/75) aimed for 1.5–3 g/kg/d of amino acids, whereas 27% (20/75) aimed for 2–3 g/kg/d. Eighty-three percent (63/76) aimed for a dose of 2.5g–3.5 g/kg/d of lipids; about 9 % (7/76) targeted a dose of 1–2.5 g/kg/d and 4% (3/76) for >3.5 g/kg/d ( 20 ). Data in our study showed that over half of the late preterm infants were given parenteral nutrition support for at least one day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the prescription of parenteral nutrition, 61% (46/75) aimed for 1.5–3 g/kg/d of amino acids, whereas 27% (20/75) aimed for 2–3 g/kg/d. Eighty-three percent (63/76) aimed for a dose of 2.5g–3.5 g/kg/d of lipids; about 9 % (7/76) targeted a dose of 1–2.5 g/kg/d and 4% (3/76) for >3.5 g/kg/d ( 20 ). Data in our study showed that over half of the late preterm infants were given parenteral nutrition support for at least one day.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the 1st week, infants on parenteral nutrition decreased to 10–40%. The composition of parenteral nutrition prescribed varied from intravenous infusion of carbohydrates alone to combinations of dextrose, lipids, and amino acids in addition to minerals and vitamins ( 16 , 20 ). Infants were prescribed with amino acid at 1.5–2.5 g/kg/d and lipid emulsion at 1.5–2.0 g/kg/d at the end of the 1st week.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a survey (September 2019) to find the current practice and to seek the opinions of clinicians (neonatologists and paediatric intensivists) in Australia and New Zealand [70]. We found that 43% of respondents (32/74) thought that commencing parenteral amino acids "within 24 h of admission" is beneficial, while 32% (24/74) felt that late commencement "after 72 h" is optimal.…”
Section: Justifications For the Definition Of 'Late Pn' (Intervention...mentioning
confidence: 99%
“…Similarly, 41% (31/75) thought that commencement of parenteral lipids "within 24 h of admission" is optimal, whereas 35% (26/74) felt late commencement "after 72 h" to be beneficial. Only one respondent thought "after 7 days of admission" was an optimal time to commence lipids [70].…”
Section: Justifications For the Definition Of 'Late Pn' (Intervention...mentioning
confidence: 99%
See 1 more Smart Citation